Impact of Physical Classrooms Environment and Teaching Methods on Learning Experiences of University Students - Rasheed, Sidra; Shoukat, Syeda Lubna (Pakistan Journal of Humanities and Social Sciences, 2024)
The objectives of the study were to find out students’ learning experiences regarding the physical environment of classroom at university level and to determine students’ learning experiences about different teaching methods used in classroom at university level. This study was descriptive and quantitative in nature in which a questionnaire was developed. The population of the study was consisted of three public and private universities of Bahawalpur and Multan. The total sample was 600 students (300 males and 300 females).The sample were selected by using convenient sampling techniques. A questionnaire was self-developed and used as a tool for data collection, and every question was answered in the form of multiple responses. Most of the respondent agreed that the proper sitting space is most suitable for their work in their classroom, and most agreed that the lecture method is most effective method in their learning. It was suggested that the learning of students could be enhanced by providing a better physical classroom environment and using innovative and modified teaching methods in classroom during teaching learning process.